2010
DOI: 10.1590/s0104-56872010000300019
|View full text |Cite
|
Sign up to set email alerts
|

Manifestações audiológicas em crianças e adultos com AIDS

Abstract: children and adults with AIDS present alterations in audiological assessment and Auditory Brainstem Response. This suggests the involvement of peripheral and central auditory pathways. Findings of the present study emphasize the effectiveness of using electrophysiological hearing measures in order to better identify the brain injury level in patients with AIDS, besides allowing the monitoring of the development rate of the disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
23
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 13 publications
3
23
1
Order By: Relevance
“…These findings confirm different studies in the literature that have shown the presence of significant impairment in HFA (9,21,26) . In a study that assessed 25 subjects with HIV, it was found that 88% of the cases had abnormal HFA results (21) .…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…These findings confirm different studies in the literature that have shown the presence of significant impairment in HFA (9,21,26) . In a study that assessed 25 subjects with HIV, it was found that 88% of the cases had abnormal HFA results (21) .…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, the authors have noticed higher occurrence of sensorineural hearing loss compared to conductive loss in the CPTA, demonstrating the inner ear impairment in this population. The obtained results confirmed one study in which the author, to characterize the results of audiologic assessment in children and adults with HIV/AIDS, observed higher occurrence of conductive hearing loss in children (92.9% of the cases), whereas in the adult population there was higher occurrence of sensorineural hearing loss (44.4% of the cases) (26) . Upon comparing the subjects with HIV/AIDS submitted and not submitted to antiretroviral therapy, the data observed in the present study showed that there were no differences in occurrence of hearing loss in these two groups, confirming the results of some specific studies in the area (14,19,20) , and disagreeing with other studies that correlated the use of antiretroviral medication with higher occurrence of hearing impairment (5,9,(15)(16)(17)(18)21) .…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Another study (7) reports a higher prevalence of hearing loss (59.4%) in children and adolescents with HIV/AIDS, in addition to alterations in the central auditory pathways (5,6) . As hearing loss increases in severity, vocabulary, phonological awareness, auditory discrimination, and school achievement declines, and the incidence of articulation difficulties, changes, and omissions increases (10) .…”
Section: Acquired Immunodeficiency Syndrome (Aids) Is An Infectious Amentioning
confidence: 99%
“…Studies (3)(4)(5)(6)(7) suggest that children with HIV are especially vulnerable to hearing disorders. Hearing loss hampers or destroys oral communication, which has direct repercussions on the social and family environments.…”
Section: Acquired Immunodeficiency Syndrome (Aids) Is An Infectious Amentioning
confidence: 99%